Histomorphology, histochemistry and micrometrical study of the testes of Tom cat - Patel, Maitri J; Panchal, Kantilal M; Gaikwad, Pradnya N; Gori, Harish P; Patel, Ritu J (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present research work was carried out on testes procured from six healthy adult nondescript male cats brought for castration/neutering at Veterinary Clinical Complex as well as Department of Veterinary Surgery & Radiology, College of Veterinary science and Animal Husbandry, Kamdhenu University, Anand, Gujarat. The fibrous connective tissue capsule of testes was made up of outer tunica albugenia and inner tunica vasculosa. The tunica albugenia was thinner as compared to tunica vasculosa layer. The capsule was having collagen fibers and sparce number of elastic fibers. Mean thickness of tunica albuginea was 38.35±1.42 µm. The mediastinal testis was located centrally in the testicular parenchyma. The rete testis was lined by simple cuboidal epithelial cells, presenting prominent oval and horizontally placed nuclei in it. Each lobule of testis was having two to five seminiferous tubules which were oval to coiled irregular in shape. The mean diameter of seminiferous tubules was 243.37±2.52 µm whereas the mean height of spermatogenic epithelium of seminiferous tubules was 65.52±0.77 µm. There was average 17-18 Sertoli cells noticed per cross section of seminiferous tubules. The mean height of Sertoli cells was 38.35±1.42 µm. Clusters of Leydig cells were arranged in triangle or rectangle or irregular shape in the interstitial spaces. There was presence of lipid material in the Leydig cells. The mean diameter of Leyding cells was 7.4 µm. The elongated myoid cells were found at the basement membrane of the seminiferous tubules. The tunica albuginea, basement membrane of seminiferous tubules and mediastinal testis were strongly positive for PAS Alcian blue stain indicated more amount of neutral mucopolysaccharides. The seminiferous tubular epithelial cells and interstitial cells were moderately positive for neutral mucopolysaccharides.
Keywords: Cat; Histochemistry; Histomorphology; Micrometry; Testis